ANALISIS PENERAPAN HUKUM PERSAINGAN USAHA ATAS KETERLAMBATAN NOTIFIKASI AKUISISI SAHAM: STUDI KASUS PERKARA NOMOR 12/KPPU-M/2023 - Muhamad Afifullah (Fakultas Hukum Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Competition law in Indonesia plays an important role in maintaining fairness and business efficiency. Under Law No. 5/1999, business actors are required to notify KPPU in the case of share acquisitions, ensuring that the activity does not damage the competitive structure of the market. In the Pon Holdings B.V. case, KPPU imposed a fine of Rp1,250,000,000 due to a one-day delay in notification. Although small, this violation shows KPPU's commitment to maintaining legal compliance. Time relaxation through KPPU Regulation No. 3/2020 adds flexibility, but presents new challenges. This case is a reflection of the development of the competition law system in Indonesia in maintaining a healthy and attractive business ecosystem. This research uses normative juridical method with literature study. The first finding is that business competition has been regulated by Singapore and the United States since before the 1990s, while Indonesia has only regulated it since the IMF agreement in 1998. The second finding is that the one-day delay in notification by Pon Holdings B.V. violates Article 29 of Law Number 5 Year 1999 and Article 5 of Government Regulation Number 57 Year 2010, emphasizing the importance of acquisition notification compliance. The Rp1,250,000,000 sanction reflects the principle of proportionality, considering the delay, market impact, and cooperative attitude of the reported party. The relaxation of notification time in KPPU Regulation Number 3/2020 provides flexibility, but still requires strict supervision. This case warns business actors that administrative violations have legal consequences. System digitization, socialization, and evaluation of time limits are needed to improve compliance and maintain fair business competition. Then, of course, this business behavior violates the principle of good faith and KPPU has implemented legal certainty.